Mechanism of Alkali-Activated Copper-Nickel Slag Material. (22nd January 2020) - Zhang, Tingting; Jin, Haoliang; Guo, Lijie; Li, Wenchen; Han, Junan; Pan, Andrew; Zhang, Dan
Abstract : A copper-nickel slag-based alkali-activated cementing material (CNSCM) for backfilling was prepared using copper-nickel slag as a raw material and sodium silicate (SS) as an activating agent. The effects of SS content (6%, 8%, and 10%) and curing humidity on the compressive strength of CNSCM were investigated using an electronic universal testing machine. Types of hydration products and microstructures were analyzed by X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The results indicated that by increasing the SS content, the compressive strength of the CNSCM exhibited an increasing trend, followed by a decreasing trend. The optimal content was 8%. Humidity was identified as another factor affecting compressive strength, which reached 17 MPa after curing for 28 d under standard conditions. A decrease in humidity could improve the compressive strength of the material. The main hydration reaction products of the CNSCM were C-S-H gel, Fe (OH)2 or Fe (OH)3 gel, and CaCO3 .